Morphology engineering of LiFeO2 nanostructures through synthesis controlling for electrochemical hydrogen storage inquiries. (1st April 2022) - Yousif, Qahtan A.; Ranjeh, Mahdi; Ghiyasiyan-Arani, Maryam; Al-Nayili, Abbas; Monsef, Rozita; Salavati-Niasari, Masoud
Abstract: The nanostructures of LiFeO2 were fabricated by Pechini procedure using comparative fuels (EDTA, citric acid and tartaric acid) to select ideal morphology and structural characters. The pH (6, 8 and 12) for mixture medium is another parameter studied in terms of the effect on the structural characterization. Also, the calcination temperature was studied on the morphology of samples. The ideal product with rod shape was chosen to compare with the particle-shaped product through charge–discharge electrochemical hydrogen sorption capability. The calculated discharge capacity for rod-shaped LiFeO2 is 410 mAhg −1 . However, the discharge capacity for nanoparticles of LiFeO2 was calculated at about 302 mAhg −1 . The magnetic, electrochemical and structural analyses were performed to investigate the properties of LiFeO2 nanostructures.